The influence of green ergonomic factors on physical environmental conditions and fish smoking processing efficiency - Ainun Mirza Nurhaniefa; Imas Cintamulya (JPBIO (Jurnal Pendidikan Biologi), 2022)
Several studies have been carried out related to fish smoking processing centers that have caused environmental problems, but none have linked the green ergonomics factor as a solution to these problems. The purpose of this study was to determine the relationship between the influence of ergonomic factors on physical environmental conditions and processing efficiency at the Fish Smoking Center of Plaza Ikan Karangsari Tuban. This study used the PLS-SEM analysis technique to describe the relationship between the influence of green ergonomic factors on physical environmental conditions and processing efficiency. The data were analyzed using the SmartPLS technique to evaluate the measurement model and structural model. According to the data analysis, it was found that at Plaza Ikan Karangsari Tuban, the ergonomic factors do not have significant effect on processing efficiency with a statistical t value of 0.422. The ergonomic factors have a significant effect on the work environment with a t statistic of 5.305 and processing efficiency with a t statistic of 2.608. Thus, it can be concluded that the green ergonomic factors in the fish smoking center at Karangsari Tuban do not have significant effect on processing efficiency and have a significant effect on physical working environment conditions.